Catalase Activity of Sulfate-Reducing Bacteria Desulfovibrio piger Vib-7 and Desulfomicrobium sp. Rod-9 Isolated from Human Large Intestine - Kushkevych, Ivan V; Fafula, Roman V; Antonyak, Halyana L (Microbes and Health, 2014)
Catalase activity of the sulfate-reducing bacteria Desulfovibrio piger Vib-7 and Desulfomicrobium sp. Rod-9 isolated from the human large intestine was studied. The high activity of the enzyme in cell-free extracts of both bacterial strains was determined (1745.21±154.67 and 873.11±72.23 U×mg-1 protein for D. piger Vib-7 and Desulfomicrobium sp. Rod-9, respectively). The effect of different temperature and pH as well as H2O2 concentration and time of incubation on the catalase activity in the cell-free extracts of D. piger Vib-7 and Desulfomicrobium sp. Rod-9 were examined. The maximum catalase activity for both bacterial strains at +30ºC temperature was determined. The highest activity of the studied enzyme in the cell-free extracts of D. piger Vib-7 at pH 7.5 and Desulfomicrobium sp. Rod-9 at pH 7.0 was measured. Based on experimental data, the analysis of the kinetic properties of the catalase by the studied bacteria was carried out. Increasing of hydrogen peroxide concentrations from 0.5 to 5.0 mM causes a monotonic rise of studied enzyme activity and the activity was maintained on an unchanged level (plateau) under substrate concentrations over 5.0 mM. The catalase activity, initial (instantaneous) reaction rate (V0) and maximum rate of the catalase reaction (Vmax) were significantly higher in D. piger Vib-7 than in Desulfomicrobium sp. Rod-9 cells. Michaelis constants (Km) of the catalase reaction were 8.01±0.77 and 10.33±0.98 mM for D. piger Vib-7 and Desulfomicrobium sp. Rod-9, respectively. DOI: http://dx.doi.org/10.3329/mh.v3i1.19776 Microbes and Health, June 2014. 3(1): 15-20